Anti-NMDA-receptor Encephalitis in an Adolescent With HIV Infection and Review of the Literature. Issue 8 (August 2019) - Pinzon-Charry, Alberto; Wallace, Geoff; Clark, Julia E.; Nourse, Clare
Abstract : Anti-N-Methyl-D-Aspartate-receptor encephalitis is the most common antibody-mediated autoimmune encephalopathy. A HIV-infected African boy presented with subacute psychosis as manifestation of anti-N-Methyl-D-Aspartate-receptor encephalitis. Intravenous immunoglobulin and corticosteroids induced complete remission. Although this is the first pediatric case described, 5 adult cases have been reported. The role of HIV in the etiology of this autoimmune condition requires further exploration.